La révolution automobile - Bardou, Jean-Pierre; Chanaron, Jean-Jacques; Fridensen, Patrick; Laux, James M. (Paris: Albin Michel, 1977)
"Jean-Pierre Bardou, Jean-Jacques Chanaron, Patrick Fridensen, James M. Laux Bibliotheek François Vercammen"